2012
DOI: 10.1182/blood-2011-10-385989
|View full text |Cite
|
Sign up to set email alerts
|

The zebrafish reveals dependence of the mast cell lineage on Notch signaling in vivo

Abstract: We used the opportunities afforded by the zebrafish to determine upstream pathways regulating mast cell development in vivo and identify their cellular origin. Colocalization studies demonstrated zebrafish notch receptor expression in cells expressing carboxypeptidase A5 (cpa5), a zebrafish mast cell-specific marker. Inhibition of the Notch pathway resulted in decreased cpa5 expression in mindbomb mutants and wild-type embryos treated with the ␥-secretase inhibitor, Compound E. A series of morpholino knockdown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 45 publications
0
23
1
2
Order By: Relevance
“…Thus, the enhancing effect of N2 ICD on cytokine production was modest in BMMCs, probably due to the adverse effect of the excessive signaling caused by overexpression of N2 ICD . Although Da'as et al (42) have reported that zebrafish notch1b regulates mast cell development through gata2, previous reports by Sakata-Yanagimoto et al (16,17) and our results indicate that mouse Notch2 but not Notch1 is involved in mast cell development. Notch2 signaling-induced downregulation of SHIP-1 may contribute to the differentiation of mast cells and the enhancement of multiple cytokine production in mice.…”
Section: Discussioncontrasting
confidence: 38%
“…Thus, the enhancing effect of N2 ICD on cytokine production was modest in BMMCs, probably due to the adverse effect of the excessive signaling caused by overexpression of N2 ICD . Although Da'as et al (42) have reported that zebrafish notch1b regulates mast cell development through gata2, previous reports by Sakata-Yanagimoto et al (16,17) and our results indicate that mouse Notch2 but not Notch1 is involved in mast cell development. Notch2 signaling-induced downregulation of SHIP-1 may contribute to the differentiation of mast cells and the enhancement of multiple cytokine production in mice.…”
Section: Discussioncontrasting
confidence: 38%
“…According to the literature, zebrafish early mast cells could be distinguished at 28 hpf (Da'as et al ., ; Dobson et al ., ). In the initial assay development, we measured tryptase relative activity in zebrafish at six various developmental stages: 2, 3, 4, 5, 6 and 7 dpf in a microplate‐based assay using BAPNA as a substrate and found that tryptase activity increased as zebrafish developed, indicating that tryptase is measurable in larval zebrafish (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Zebrafish mast cells have similar structure and functions to mammals, and are involved in the body's immune response and allergic reaction (Dobson et al ., ). Zebrafish has been used as a model to study mast cell development and functions (Da'as et al ., ; Dobson et al ., ). Da'as et al .…”
Section: Introductionmentioning
confidence: 97%
“…Moreover, Notch2 signaling in MC is required for proper localization of intestinal MC during murine parasitic infection [24]. A transgenic zebrafish line overexpressing notch1a recapitulated the MC accumulation observed in human systemic mastocytosis and was abrogated upon Notch pathway inhibition, also suggesting the dependence of human MC lineage on Notch signaling [25]. Although both gata2 and pu.1 are critical to MC lineage commitment, gata2 is controlled by the Notch signaling pathway, whereas pu.1 appears to be more selectively regulated by notch1a [25].…”
Section: MC Plasticity In Development and Maturationmentioning
confidence: 99%
“…A transgenic zebrafish line overexpressing notch1a recapitulated the MC accumulation observed in human systemic mastocytosis and was abrogated upon Notch pathway inhibition, also suggesting the dependence of human MC lineage on Notch signaling [25]. Although both gata2 and pu.1 are critical to MC lineage commitment, gata2 is controlled by the Notch signaling pathway, whereas pu.1 appears to be more selectively regulated by notch1a [25]. A recent study demonstrated that complete gata1 ablation had minimal effects on MC numbers and tissue distribution in adult mice but reduced MC tryptase expression levels [26].…”
Section: MC Plasticity In Development and Maturationmentioning
confidence: 99%